#### Answer

C

#### Work Step by Step

$y=x^2-6$ shifted 3 units down
Let $x=0$
$y=x^2-6$
$y=0^2-6$
$y=0-6$
$y=-6$
$(0,-6)$ would be shifted to $(0,-9)$
$y=x^2-b$
$-9=0^2-b$
$-9=0-b$
$b-9=0$
$b=9$
$y=x^2-9$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

C

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.